A new genus and species of Anchitrematidae Mehra, 1935 (Digenea: Gorgoderoidea) in a freshwater fish from the River Nile at Qena, Egypt with amendation of the family - Dronen, Norman O.; Karar, Yasser F. M.; Blend, Charles K. (Zootaxa, 2020)
Museum specimens of a previously unknown species of the Anchitrematidae from a freshwater fish collected from the River Nile at Qena, Egypt were examined. This species is somewhat similar to species of Anchitrema, but was found to have a thick, continuous, shelf-like rim around the periphery of the ventral aspect of the distome, the lateral aspect of the forebody was composed of large internal patches of lightly vacuolated, somewhat glandular cells that formed pad-like structures (pelops-like structures), and it possessed a uterine seminal receptacle; characteristics that previously have not been found in any species in the family. Species currently assigned to Anchitrema or Mujibia (the only two genera in the family) are known only from reptiles and mammals and no species has previously been reported from a freshwater fish. We feel that these differences are sufficient enough to warrant the erection of Piscianchitrema n. gen. and amendation of the family. We support the synonymies of Anchitrema congolense with Anchitrema latum, and Anchitrema lucknowensis with Anchitrema indicum. The current status of species previously described in the family is discussed, and keys to the genera and species of Anchitrema are provided.